Brain functional changes in individuals with bulimia nervosa: a protocol for systematic review and meta-analysis. Issue 4 (5th April 2022) - Sun, Yiming; Ye, Q; Wen, Q; Liu, X R; Sun, R; Dai, Y
Abstract : Introduction: Bulimia nervosa (BN) is a disorder with high health and socioeconomic burdens that typically arises in late adolescence and early adulthood. Previous neuroimaging studies have found functional brain changes in patients with BN. This study aims to review the latest neurobiological evidence from studies of individuals with BN, examine the consistency of these findings and evaluate the food addiction hypothesis of the disease. Methods and analysis: A systematic search will be performed using the Cochrane Library, PubMed, Embase and Web of Science databases, covering the period from database inception to 30 November 2021. Two researchers will be responsible for study selection, quality assessment and data extraction. The anisotropic effect size version of the signed differential mapping method will be used to conduct a coordinate-based meta-analysis. Publication bias will be examined with the Egger test. The quality of studies will be evaluated using the Newcastle-Ottawa Scale. Ethics and dissemination: No ethics approval is required for this is a systematic review protocol and does not require the collection of primary data. Findings will be disseminated through peer-reviewed journal or related conferences. PROSPERO registration number: CRD42022307233.